Mentoring in libraries and information organisation, the catalogue librarian perspectives - Bello, M.A; Mansor, Yushiana (University of Nebraska--Lincoln Libraries, 2013)
All professions engage in continuous training in order to sharpen and sustain professional practice, standards as well as keep abreast with challenges and developments. Mentoring as career development model provides professional development, career growth, confidence, satisfaction as well as develops varied degrees of personal support. The present study is a survey of 48 Nigerian university catalogue librarians’ opinions on the use of mentoring in their professional practice. Questionnaire was used to collect data from 228 participants. The study explores the mentoring practices and assessment in Nigerian university libraries. Survey was conducted from April to September 2011 across Nigerian 36 states. Findings show that Nigerian university libraries practise different types of mentoring programmes with supervisory model being most popular. All the respondents appraised the programme to be satisfactory. Therefore, library management needs to actively promote the programme and give it deserves consideration.